The Implementation of A Multiliteracy Pedagogy Framework for Teaching Critical Teaching - Ana Christanti; Susanto; Ahmad Munir (CV. AFDIFAL MAJU BERKAH, 2023)
The Multiliteracy Pedagogy Framework has been promoted to improve education in many countries; however, it is not popular yet in Indonesia. The framework relates to enhancing students' thinking skills. The other research indicated that the MPF did not positively affect students' critical thinking since the teacher did not have good knowledge about it; the teacher did not completely implement the four framework syntax in the teaching-learning process. The research, therefore, intends to reveal the implementation of the MPF for teaching critical thinking in the reading class of English Language Education (PBI) students. The research subjects are a lecture on the Reading subject and 20 students in the third semester at PBI Nahdlatul Ulama University of Sidoarjo (UNUSIDA). It is descriptive qualitative research using observation and questionnaire techniques to collect data. Descriptive statistics were used to generate summaries. The first implementation process is changing the lesson plan based on the multiliteracy pedagogy framework dimension. The activities are arranged in order from the cognitive functions in Multiliteracy; experiencing, conceptualizing, analyzing, and applying. The lecturer followed the syntax easily and completely. The result of students' assignments proves they can think critically about a text by giving comments supported with reasons, recommendations, data, conclusions, and evaluations. Besides, the students enjoyed the instruction and responded well to the questionnaire, with 96,5% on average.